Early Marriage among Generation Z Women in Indonesia: A Systematic Literature Review - Intan Agilliana; Aryani Dwi Kesumawardani; Rizka Fatiha Salma; Wahyu Igo Pratama (WISE Pendidikan Indonesia, 2024)
This study systematically reviews research on early marriage among Generation Z women in Indonesia between 2014 and 2024 using the PRISMA 2020 framework. A total of 1,100 records were identified across Scopus, Google Scholar, and ScienceDirect databases, with 19 eligible studies analyzed thematically. The findings indicate that cultural traditions, educational inequality, economic insecurity, and digital media exposure interact to sustain early marriage practices. Despite modernization, patriarchal norms and social expectations persist, particularly in rural and low-income regions. Education remains a key protective factor, whereas low digital literacy and online misinformation exacerbate risky decisions regarding marriage readiness. The study introduces a novel “Digital-Cultural Intersection Model,” demonstrating how social media shapes generational identity and marriage perception among Indonesian youth. The review highlights the need for integrated interventions that combine gender-sensitive education, digital literacy, and socio-economic empowerment. It concludes that early marriage among Generation Z women is a multidimensional adaptation to cultural and digital realities requiring holistic preventive policies.